AB0375 HYPOGAMMAGLOBULINEMIA AFTER RITUXIMAB TREATMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS IS NOT RARE AND IS ASSOCIATED WITH BETTER RESPONSE. (June 2019) - Evangelatos, Gerasimos; Fragoulis, George E.; Klavdianou, Kalliopi; Vassilopoulos, Dimitrios; Iliopoulos, Alexios
Abstract : Background: Rituximab (RTX) is used as a second line treatment in rheumatoid arthritis (RA), with well-established efficacy. One of the most common adverse events of RTX use is hypogammaglobulinemia (HGG). Objectives: To define, in RA patients treated with Rituximab, the frequency of HGG (IgG<700mg/dL or IgM<40mg/dL or IgA<70mg/dL) and to identify associations between its occurrence and clinical, epidemiological and other disease related features at baseline, RA outcomes and adverse events. Methods: The patients received RTX for RA in two rheumatology centers from 1/2007 to 12/2018 were included. Demographical, clinical and laboratory parameters were recorded at baseline and at the last visit of the follow-up. Time of follow-up was defined as the time interval between the first RTX infusion and the last visit. Patients with monoclonal gammopathy and patients that received only one cycle of treatment were excluded. Severe infections were recorded defined as those which required hospitalization or antibiotics intravenously. Binomial regression analysis using stepwise backwards model having as dependent variables the "low IgG" or "low IgM" and independent variables: gender, age, follow-up duration, RF levels, number of cycles received, DAS28(CRP) at baseline and IgG or IgM levels at baseline. SPSS software 21.0 and GraphPad Prism 5.00 were used for statistical analyses. Results: 76 patients were included followed up for a median (range) of 48 (6-135) months. 65 were female (84.4%) with a mean±SD age of 63.5±11.8 and baseline DAS28(CRP) of 5.98±1.25. 67.8% and 65.2% of patients were RF positive, respectively (Table). At baseline, none of them had low IgG or IgA levels while 4 patients had IgM levels below 40mg/ml. The patients received median (range) 8 (2-20) cycles of RTX. In total, 43.4%, 25%, 28.9% and 5.3% developed HGG, low IgG, IgM and IgA, respectively. In 15.8% of the patients, at least 2 immunoglobulins subclasses were low. Levels of IgG and IgM, at the last visit, were negatively correlated with the number of RTX cycles received (IgG: p=0.02, r=-0.27; IgM: p=0.03, r=-0.25). At baseline, no differences were recorded between patients that developed HGG and those who did not (Table). Patients who developed low IgG or IgM had lower baseline levels of IgG or IgM levels, respectively (Table). Multivariable analyses revealed number of cycles received (p=0.03) and baseline IgM levels (p=0.03) as predictors of "low IgM" occurrence, while no variable was identified for "low IgG". At the end of follow up, the patients who developed HGG or low IgM compared to those who did not, exhibited lower DAS28 (Table). Concurrent treatment, during follow up or at the time of the last visit did not differ between the various groups, except from co-administration of methotrexate, which was more frequent at the time of last visit in patients who did not develop HGG (43.5% Vs 30.3%, p=0.04). No difference was observed in infections rate, among all analyses performed. Conclusion: HGG following RTX can be developed in about 40% of RA patients even after several treatment cycles. It is related to baseline immunoglobulin levels and possibly combined with better disease outcomes. The latter is observed primarily with IgM. No increased risk of major infections was identified. Disclosure of Interests: None declared